Management information systems managing the digital firm - Laudon, Kenneth C. 1944- (Pearson Education Limited, 2012)
Directed primarily toward undergraduate CIS/MIS college/university majors, this text also provides practical content to current and aspiring industry professionals. Management Information Systems provides comprehensive and integrative coverage of essential new technologies, information system applications, and their impact on business models and managerial decision making in an exciting and interactive manne